Karyology and Genome Size Analyses of Iranian Endemic Pimpinella (Apiaceae) Species - Mehravi, Shaghayegh; Ranjbar, Gholam Ali; Najafi-Zarrini, Hamid; Mirzaghaderi, Ghader; Hanifei, Mehrdad; Severn-Ellis, Anita Alice; Edwards, David; Batley, Jacqueline (Frontiers in Plant Science, 2022)
Pimpinella species are annual, biennial, and perennial semibushy aromatic plants cultivated for folk medicine, pharmaceuticals, food, and spices. The karyology and genome size of 17 populations of 16 different Pimpinella species collected from different locations in Iran were analyzed for inter-specific karyotypic and genome size variations. For karyological studies, root tips were squashed and painted with a DAPI solution (1 mg/ml). For flow cytometric measurements, fresh leaves of the standard reference (Solanum lycopersicum cv. Stupick, 2C DNA = 1.96 pg) and the Pimpinella samples were stained with propidium iodide. We identified two ploidy levels: diploid (2x) and tetraploid (4x), as well as five metaphase chromosomal counts of 18, 20, 22, 24, and 40. 2n = 24 is reported for the first time in the Pimpinella genus, and the presence of a B-chromosome is reported for one species. The nuclear DNA content ranged from 2C = 2.48 to 2C = 5.50 pg, along with a wide range of genome sizes between 1212.72 and 2689.50 Mbp. The average monoploid genome size and the average value of 2C DNA/chromosome were not proportional to ploidy. There were considerable positive correlations between 2C DNA and total chromatin length and total chromosomal volume. The present study results enable us to classify the genus Pimpinella with a high degree of morphological variation in Iran. In addition, cytological studies demonstrate karyotypic differences between P. anthriscoides and other species of Pimpinella, which may be utilized as a novel identification key to affiliate into a distinct, new genus – Pseudopimpinella.